Assessment of the prevalence of polycystic ovary syndrome among the college students: A case-control study from Kolkata - Madhumati Chatterjee; Soma Aditya Bandyopadhyay (Wolters Kluwer Medknow Publications, 2020)
Background: Polycystic ovary syndrome (PCOS) is one of the most common endocrine disorders in women of reproductive age. Of late, the disease is on its rise due to environmental changes as well as lifestyle disorders, affecting 4%-26% of adolescent and young women all over the globe. Initially, this condition is asymptomatic in young girls, progressing toward menstrual irregularities, obesity, hyperandrogenism in late puberty and eventually developing insulin resistance, hypertension, type 2 diabetes, cardiovascular diseases, and infertility around middle age. Aims: Early diagnosis is necessary for early intervention, including lifestyle modifications to prevent the immediate and chronic consequences of PCOS. Materials and Methods: Our study design was of a cross-sectional questionnaire-based survey, conducted from September 2017 to March 2018 to investigate the prevalence of PCOS and its association with body composition variables. The study population comprised randomly chosen students (age group 18-20 years) of all discipline. The data were collected from the students using structured questionnaire with Rotterdam's criteria, and anthropometric measurements were taken using standard techniques. Results: Approximately 28% of the college students were found to be at high risk of developing PCOS. More than 85% of the PCOS cases had oligomenorrhea, 19% were hirsute, 41% had acne, 63% had emotional disturbance, and 22% with a positive family history. Furthermore, the body mass index of the PCOS students demonstrated a trend of Grade 1 obesity than the normal females of the same age group. Conclusion: The present study is an attempt to create increased awareness among the students for early and accurate diagnosis, which is the primary step in managing PCOS.